2009
DOI: 10.1007/s00436-009-1513-y
|View full text |Cite
|
Sign up to set email alerts
|

Expression of cytokines and chemokines and microvasculature alterations of the tongue from patients with chronic Chagas’ disease

Abstract: Chagas' disease is caused by the protozoan Trypanosoma cruzi and continues to be a significant public health problem, since 10 million people are still infected in Latin America. The purpose of this study was to analyze the microvasculature alterations as well the expression of cytokines and chemokines in the tongues from patients with chronic Chagas' disease (CC; n = 18), comparatively with a non-chagasic group (NC; n = 22). We observed several vascular alterations in the tongue of CC such as a greater vascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Thus, the fact that the tongue does not present significant functional alterations answers a series of questions that have arisen in the development of several studies carried out by this team (Pereira et al, 2006;Pereira et al, 2007;Pereira et al 2009). However, it is clear that the present study presents limitations, such as the relatively small number of patients, since many of the patients that attended the clinic did not present CD or did not agree to participate in the study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the fact that the tongue does not present significant functional alterations answers a series of questions that have arisen in the development of several studies carried out by this team (Pereira et al, 2006;Pereira et al, 2007;Pereira et al 2009). However, it is clear that the present study presents limitations, such as the relatively small number of patients, since many of the patients that attended the clinic did not present CD or did not agree to participate in the study.…”
Section: Discussionmentioning
confidence: 99%
“…The tongue plays an essential role in deglutition (Felton et al, 2007). Previous studies have shown that in chronic chagasic patients the tongue presents several microscopic morphological alterations, such as increased vascular diameter, increased vascular wall area, increased blood vessel density, increased thickening of the basal capillary membrane (Pereira et al, 2009), as well as a higher percentage of collagen and higher density of mast cells (Pereira et al, 2007). Parasitism of the skeletal muscle in the chronic phase also triggers repair mechanisms through collagen deposition resulting in alterations in muscle contractility (Novaes et al, 2016).…”
Section: Introdutionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the heart muscles, other muscles can be infected in human CD, such as the gastrocnemius (Lugo de Yarbuh et al 2006) and lingual muscles (Barbosa and Andrade 1984). Recent studies by our group have shown that the tongues of individuals with CD exhibit more significant morphological changes when compared with patients without CD (de Lima Pereira et al 2006Pereira et al , 2007Pereira et al , 2009.…”
Section: Introductionmentioning
confidence: 94%
“…Therefore, since the tongue is an organ of easy access and presents resistance to decomposition and carbonization because it is located in a humid closed cavity, it has become an important organ in postmortem evaluation [7,8].…”
Section: Introductionmentioning
confidence: 99%